Integrating PjBL and service-learning to improve 21st-century skills in tourism education - R. Rosita; Armandha Redo Pratama; Erry Sukriah; Rudi Susilana; R. Rusman (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
Students must master 21st-century skills in preparation for success in a digital society. The development of these skills is closely related to deep learning, such as analytical reasoning, problem-solving, and teamwork. Learning models such as PjBL and service-learning are two constructivist learning models that have the potential to improve student learning outcomes in all cognitive, affective, and psychomotor aspects. This research aimed to assess tourism students’ learning outcomes in these three aspects in one of the courses that integrate PjBL and service-learning. The assessment results showed optimal learning outcomes in all three aspects of competency. These findings support the results of previous studies regarding the effectiveness of using PjBL and service-learning. Achieving optimal learning outcomes using these two learning models requires teachers who are ready to be open to changes in teaching practices, and flexible in planning students' learning experiences. However, there are still several significant obstacles in the implementation process that need further research. AbstrakKeterampilan abad 21 harus dikuasai siswa sebagai persiapan untuk sukses dalam masyarakat digital yang berubah cepat. Pengembangan keterampilan ini terkait erat dengan pembelajaran mendalam, seperti penalaran analitik, pemecahan masalah, dan kerja tim. Model pembelajaran seperti PjBL dan service-learning merupakan dua model pembelajaran konstruktivis yang memiliki potensi meningkatkan capaian pembelajaran siswa di semua aspek kognitif, afektif, dan psikomotorik yang mendukung keterampilan abad 21. Penelitian ini bertujuan mengevaluasi capaian pembelajaran mahasiswa di ketiga aspek tersebut pada mata kuliah yang menerapkan penggabungan PjBL dan service-learning di Program Studi Manajemen Resort Leisure, Universitas Pendidikan Indonesia. Hasil evaluasi menunjukkan capaian pembelajaran yang optimal di ketiga aspek kompetensi. Mahasiswa mampu mencapai tingkat teratas capaian pembelajaran baik pada aspek kognitif, afektif, maupun psikomotorik. Hal ini berarti pencapaian yang diperlukan pada tingkat yang lebih rendah pun telah berhasil dicapai. Meskipun demikian, pencapaian learning outcome yang optimal menggunakan kedua model pembelajaran ini membutuhkan pengajar yang siap bersikap terbuka terhadap perubahan dalam praktik pengajaran, dan fleksibel dalam merencanakan pengalaman belajar siswa.Kata Kunci: capaian pembelajaran; pendidikan pariwisata; project-based learning; PjBL; service-learning